2017
DOI: 10.1017/s147474721700018x
|View full text |Cite
|
Sign up to set email alerts
|

Framing and the annuitization decision – Experimental evidence from a Dutch pension fund

Abstract: We report the effects of framing and default settings in annuity demand after conducting a survey-based experiment with over 3,000 members of a Dutch occupational pension plan. The participants were asked to allocate their real projected pension accrual between a life annuity and a partial lump sum. In particular, we investigated the joint effects of consumption and investment frames and gain and loss frames. We present strong evidence for framing and default setting effects in annuity demand. We also find rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…Combining administrative and survey data, Agnew et al (2012) find that Americans who do not trust financial institutions are more likely to exercise their right to quit automatic enrollment in 401(k) savings plans than people who trust financial institutions. Based on experimental data from a Dutch pension fund, Bockweg et al (2018) show that people with greater trust in the pension fund and the pension system take up less lump sum. In line with this finding, based on survey data on the preferences of Dutch consumers, Van der Cruijsen and Jonker (2019) find that people who do not trust their pension fund are more likely to favour a lump sum over annuity-based arrangements.…”
Section: Why Is Trust Important?mentioning
confidence: 99%
“…Combining administrative and survey data, Agnew et al (2012) find that Americans who do not trust financial institutions are more likely to exercise their right to quit automatic enrollment in 401(k) savings plans than people who trust financial institutions. Based on experimental data from a Dutch pension fund, Bockweg et al (2018) show that people with greater trust in the pension fund and the pension system take up less lump sum. In line with this finding, based on survey data on the preferences of Dutch consumers, Van der Cruijsen and Jonker (2019) find that people who do not trust their pension fund are more likely to favour a lump sum over annuity-based arrangements.…”
Section: Why Is Trust Important?mentioning
confidence: 99%
“…In the Chilean setting, Hastings et al (2011) showed that people with lower levels of education, income, and financial literacy were more responsive to framing. Bockweg et al (2016) surveyed more than 3,000 members of an occupational pension plan in the Netherlands, and confirmed evidence of framing and default setting effects.…”
Section: Figure 4 Herementioning
confidence: 62%
“…A different strand of literature explores whether behavioral factors help explain low observed levels of annuitization. Several hypothetical choice experiments suggest that behavioral factors influence the demand for annuities, including studies showing that framing of the annuity choice affects the demand for annuities Wrobel, 2008, 2013;Beshears, Choi, Laibson, Madrian, and Zeldes, 2014;Brown, Kapteyn, and Mitchell, 2016;Merkle, Schreiber, and Weber, 2017;and Bockweg, Ponds, Steenbeek and Vonken, 2018). Similar findings emerge in incentivized laboratory settings (Agnew, Anderson, Gerlach, and Szykman, 2008; Gazzale and Walker, 2011).…”
Section: Introductionmentioning
confidence: 86%